User´s satisfaction of community dental care in Reynosa, Tamaulipas - Morales-Reyes, Hilda Nelly; Martinez-Vidaurri, Carlos; Mayek-Pérez, Netzahualcoyotl (Horizonte Sanitario, 2023)
Objective: To evaluate the level of satisfaction in the care received by the users of the Dental Clinic of the Universidad México Americana del Norte (DC-UMAN) Allende. Material and method: The study was descriptive, observational, cross-sectional, and prospective. In 2019, an opinion survey on the structure, proceedings, and results of the care, as well as bio-demographics of each patient was applied to 200 patients selected by convenience sampling. Results: Patients aged between 21 and 60 years (71%), women (63%), married (45%), employees/housewives (57%) and a low frequency of concomitant diseases (10%) predominated. At an older age, there was a higher frequency of concomitant diseases (r=0.26; p<0.05) and satisfaction in the service (r=0.26; p<0.05); with other concomitant diseases, patient satisfaction was lower (r=-0.39; p<0.05). Patients indicated that there is more satisfaction (from 2.6 to 5.4 times) when receiving an adequate or better service. Patient satisfaction and the quality of clinic care were positively associated (p<0.05) with simple procedures, treatment by the dentist, confidence in the quality of the services received, cost-benefit ratio, punctuality in the care and effectiveness of the dental treatment received. The standardized canonical coefficients indicated a greater contribution to user satisfaction from the facilities and infrastructure of the clinic (0.479), staff attention and administrative process (0.543), dental care (0.700), trust in care and perception of the service received (0.660) and poor relationship with age (0.078), gender (0.030), marital status (-0.040), and occupation (0.065) of the patient. Conclusion: Although the quantity and quality of the DC-UMAN service has increased and improved substantially, it is necessary to develop a continuous improvement plan to achieve total quality standards. Key words: Dental clinics; Administrative efficiency; Community dentistry; Patient satisfaction.